#TITLE_ALTERNATIVE# - Habibah (NIM : 153 03 033), Umi
Abstarct: Contamination of caesium-134 in fresh water system caused by nuclear accident isposible to generate long term radiological effect because radiocaesium can enter into the food chain. Caesium-134 in human body can be internal radiation source if people consume food contaminated with caesium-134. The cesium-134 absorption by fish is the dominant transfer route of radiocaesium from water to human being.Prediction of radionuclide transfer factor from water to fish is an important process in predicting the exposure dose to human body through food chain. In this research,catfish (Clarias sp.) were also raised in container with water medium of 500 L which had been contaminated with caesium-134 of about 4,975 MBq. As control, catfish were raised in water without caesium-134. The uptake of caesium-134 was observed by measuring the activity of caesium-134 in abdominal organs, muscle, and boneevery five days within 67 days period of sampling. The result of measurement by gamma spectrometer showed that the maximum activity of caesium-134 in total catfish sample was about 6342.,53 Bq. The maximum concentration of caesium-134 on muscle was about 87.95 Bq/gram. Catfish uptake caesium-134 from water into its body and accumulated into abdominal organ, muscle, and bone with transfer factor of values respectively were about 12.44; 10.79; 6.51. Transfer factor of total fish sample from water to catfish was about 8.62 which was found at 50th day period sampling. The validation of caesium-134 from water to catfish transport model resulted 97% correlation between the activity of caesium-134 in catfish that were calculated based on the model with the activity of caesium-134 in catfish measuredon this research. Equivalent dose/year was calculated based on the maximumconcentration of caesium-134 in muscle of catfish. By preparation process of catfish to pecel lele, the concentration of caesium-134 was reduced from 87,95 Bq/gram to 17,96 Bq/gram. The value of equivalent dose/year was received by human body consumed pecel lele from catfish lived in water contaminated with caesium-134 was about 4,975 MBq which corelated to 0,0442 mSv/year. This amount of dose contributed of 0,34% the threshold annual equivalent dose from total consumption of food that was stated on Badan Pengawas Tenaga Nuklir Regulation No. 02/ka- Bapeten/V-99 (13mSv/year). The annual intake of caesium-134 on human body who consume pecel lele with 17,96 Bq/gram caesium-134 concentration was about 0,000303. In this research, the annual of intake caesium-134 on pecel lele was lower than the permitted value (3 x 106 Bq).